Neuromodulation of the cerebellum rescues movement in a mouse model of ataxia - Lauren N. Miterko (Nature Portfolio, 2021)
Deep brain stimulation (DBS) has potential for several movement disorders. Here the authors show that DBS improves motor function in a mouse model of ataxia.